Analisis Passing Chest Pass Permainan Bola Basket Siswa Sma Negeri 10 Makassar - Fahrizal Fahrizal; Muhammad Harliawan; M. Imran Hasanuddin (Journal on Education, 2023)
The results of learning basketball passing, especially in the chest pass in the basketball game for Makassar 10 high school students, still do not understand the basic techniques of passing chest pass, the average student learning ability is also still very low, the purpose of this research is to answer the problem raised how to find out the pattern of movement passing chest pass students in basketball games, the method used in this study is the survey method in determining the sample using proportional random sampling technique. The data collection technique uses test and observation techniques or observation techniques. The data collected in this study included: a chest pass ability test. The results of the study analyze the Chest Pass Movement Pattern which is divided into three phases, namely the preparation phase, the implementation phase, and the final phase. shows that the movement pattern of passing chest pass is in the category of "very less" by 0% (0 students), the category of "less" by 24% (9 students), the category of "moderate" by 14% (5 students), the category of "good" by 54% (20 students), and the "very good" category by 8% (3 students). Based on an average score of 19.41, the ability to pass chest pass in basketball games students at SMA Negeri 10 Makassar is in the "moderate" category. The conclusions in this study indicate that the analysis of the movement pattern of passing chest pass is in the medium category